Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

see below

Asked by 6th March 2013, 10:53 AM
Answered by Expert
Answer:

Sq = 63q - 3q2

Therefore,

S1 = 63(1) - 3(1)2 = 60 = a 1

S2 = 63(2) - 3(2)2 = 126 - 12 = 114

and so on

We get, a 1 = 60

a2 = S2 - S1 = 114 - 60 = 54

Therefore, AP is 60, 54, 48, .......

a = 60 , d = -6

ap = a+(p-1)d

-60 = 60 - 6p + 6

-60 = 66 - 6p

-126 = -6p

p = 21

a11 = a+10d = 60 + 10(-6)  = 60 - 60 = 0

Answered by Expert 6th March 2013, 11:14 AM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!